Transcriptomic and Metabolomic Response to High Light in the Charophyte Alga Klebsormidium nitens - Serrano-Pérez, Emma; Romero-Losada, Ana B.; Morales-Pineda, María; García-Gómez, M. Elena; Couso, Inmaculada; García-González, Mercedes; Romero-Campero, Francisco J. (Frontiers in Plant Science, 2022)
The characterization of the molecular mechanisms, such as high light irradiance resistance, that allowed plant terrestralization is a cornerstone in evolutionary studies since the conquest of land by plants played a pivotal role in life evolution on Earth. Viridiplantae or the green lineage is divided into two clades, Chlorophyta and Streptophyta, that in turn splits into Embryophyta or land plants and Charophyta. Charophyta are used in evolutionary studies on plant terrestralization since they are generally accepted as the extant algal species most closely related to current land plants. In this study, we have chosen the facultative terrestrial early charophyte alga Klebsormidium nitens to perform an integrative transcriptomic and metabolomic analysis under high light in order to unveil key mechanisms involved in the early steps of plants terrestralization. We found a fast chloroplast retrograde signaling possibly mediated by reactive oxygen species and the inositol polyphosphate 1-phosphatase (SAL1) and 3′-phosphoadenosine-5′-phosphate (PAP) pathways inducing gene expression and accumulation of specific metabolites. Systems used by both Chlorophyta and Embryophyta were activated such as the xanthophyll cycle with an accumulation of zeaxanthin and protein folding and repair mechanisms constituted by NADPH-dependent thioredoxin reductases, thioredoxin-disulfide reductases, and peroxiredoxins. Similarly, cyclic electron flow, specifically the pathway dependent on proton gradient regulation 5, was strongly activated under high light. We detected a simultaneous co-activation of the non-photochemical quenching mechanisms based on LHC-like stress related (LHCSR) protein and the photosystem II subunit S that are specific to Chlorophyta and Embryophyta, respectively. Exclusive Embryophyta systems for the synthesis, sensing, and response to the phytohormone auxin were also activated under high light in K. nitens leading to an increase in auxin content with the concomitant accumulation of amino acids such as tryptophan, histidine, and phenylalanine.